The effect of painting on depression in children with cancer undergoing chemotherapy - Zahra Tahmasebi; Jahangir Maghsoudi; Sedigeh Talakoub (Wolters Kluwer Medknow Publications, 2017)
Background: Psychological and social health of children with cancer may be severely affected by the disease and its treatment. Successive drawing by children can help them over time in terms of psychological and social adaptation. This study aimed to investigate the effects of drawing on depression in children with cancer undergoing chemotherapy. Materials and Methods: This quasi-experimental study was conducted on 7-12-year-old children with cancer undergoing chemotherapy. After completing Maria Kovacs' Children's Depression Inventory (CDI), 65 children who had obtained scores higher than 12 were chosen as study participants and were randomly divided into two experimental and control groups. The children in the experimental group were engaged in open painting sessions for 6 weeks. After the intervention, the CDI was completed again in both the groups. The obtained data were analyzed using descriptive and inferential statistical methods, such as independent t-test, paired t-test, and Chi-square and Mann-Whitney tests. Results: There was a significant difference between the children's depression scores before and after the intervention in both the two groups (P < 0.001). Conclusions: The results showed that painting was effective in reducing depression in children with cancer undergoing chemotherapy. Therefore, painting can be used as an easy, cheap, and effective intervention by nurses to help children with cancer undergoing chemotherapy.